Pengaruh Komunikasi Pemasaran Terpadu terhadap Ekuitas Merek - Kartikasari, Nia Paramita (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2014)
This study aims to identify and explain how the influence of integrated marketing communications consists of sales promotion, personal selling, and public relations together and partially on Brand Equity. The type of this research is explanatory research and using questionnaires as research instruments that distributed to 100 respondents who are customers and stay at the Hotel in Semarang. The results showed that variables of Integrated Marketing Communications like Sales Promotion, Personal Selling, and Public Relations is together influence on brand equity. While partially, only variable Sales Promotion had a significant effect on Brand Equity.